INTEGRATION OF INFORMATION AND COMMUNICATION TECHNOLOGY IN LEARNING TO IMPLEMENTATION CURRICULUM 2013 AT JUNIOR HIGHSCHOOL IN KECAMATAN PADANG TIMUR - Mutiara Felicita Amsal; Winanda Amilia; Hade Afriansyah (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
Technology mastery is one of the most important competencies for teachers. In Permendiknas No. 16/2007 concerning Academic Qualification Standards and Teacher Competencies, there are four competencies that must be mastered by teachers, two of which are pedagogical and professional competencies. Both of these competencies are very closely related to the use of technology in learning. In curriculum 2013, every teacher is required to utilize technology in the learning process. This study aims to see the extent of the use of technology by teachers in the learning process in schools in Padang. This research is a field survey research. The subjects of this study were 60 public junior high school teachers in Padang. The research method used is quantitative descriptive percentage with data collection techniques in the form of a questionnaire in the form of a Likert scale of 5. The results obtained from this study are: (a) the use of information and communication technology by teachers in planning to get 70.1% results including the high category, (b) the use of information and communication technology by teachers in the learning process to obtain 69.1% results including high category, and (c) the use of information and communication technology in learning evaluation obtained 68.9% results included in the high category.Keyword: information and communication technology, curriculum 2013